Quality and Shelf Life of Quail Carcasses in Refrigerators with Different Packaging - Mardewi, Ni Ketut; Rukmini, Ni Ketut Sri; Rejeki, I Gusti Ayu Dewi Seri; Bangur, Matilda Setia; Koni, Mardiyanto Bora (International Journal of Contemporary Sciences (IJCS), 2024)
Quail meat is a valuable source of animal protein, but its perishable nature requires proper storage methods to prevent spoilage. This study examined the effects of storage time and packaging type on quail carcass quality. A completely randomized design with a factorial pattern was used, focusing on two factors: storage time and packaging type, including polypropylene (PP), polyethylene (PE), and plastic wrap. Variables observed were color, pH, water holding capacity, protein content, and total microbial count. Data were analyzed using ANOVA, followed by the Duncan test for significant results (P < 0.05). The results showed that quail carcasses packed with PP plastic had the best quality after 9 days of cold storage, with a pH of 6.22, water holding capacity of 51.45%, protein content of 20.59%, and microbial count of 1.2 x 10⁶ cfu/gram. PP plastic, with a thickness of 0.8 mm, proved more effective than PE plastic (0.3 mm) and plastic wrap (0.2 mm) in preventing contamination, as thicker packaging provides a tighter seal, reducing air gaps that could allow bacteria to enter. Thus, PP plastic packaging is more effective in preserving quail carcass quality during storage, offering better protection against spoilage.